Représenter la communauté dans les paroisses toulousaines (xviie-xviiie siècles). Espace et statut social - Claire Dolan (Les Cahiers de Framespa)
In Toulouse, in the 17th century, participation in political life was fundamentally connected to the notion of space. The community seems to have been structured around one principal focus: the street. In the 18th century, especially for the parish council, the territorial component of the community showed signs of weakening, and social status came to become prominent. However, outside of parish structures, the territorial component continued to mobilize the people of Toulouse.